Estimating occupation- and location-specific wages over the life cycle - Elias Ilin; Ellyn Terry (Federal Reserve Bank of Atlanta, 2021)
In this paper we develop a novel method to project location-specific life-cycle wages for all occupations listed in the Occupational Outlook Handbook from the U.S. Bureau of Labor Statistics. Our method consists of two steps. In the first step, we use individual-level data from the Current Population Survey to estimate the average number of years of potential labor market experience that is associated with each percentile of the education-level specific wage distribution. In the second step, we map this estimated average years of experience to the wage-level percentiles reported in the Occupational Employment and Wage Statistics data for each occupation and area. Finally, we develop a model capable of projecting the trajectory of wages across all possible years of experience for each occupation.
Keywords: J31; 330; wage growth; wages; experience; education; earnings; Mincer earnings function